Morphology and property control of NiO nanostructures for supercapacitor applications - Dar, Farrukh Iqbal (Springer, 2013)
We process one-dimensional (1D) NiO nanostructures in anodized alumina templates starting from electrochemically deposited Ni nanotubes (NTs), and characterize their morphology-dependent supercapacitance behavior. The morphology of the 1D NiO nanostructures is controlled by the time of annealing at 450°C. After 25 min of annealing, the NTs start to close but maintain the tubular structure, and after a further 300 min of annealing time, the tubes are completely closed and nanorods (NRs) are formed. We show that the structures obtained are highly promising for supercapacitor applications; the performance of the NiO NT structure is with a specific capacitance of 2,093 F/g, the highest ever obtained for NiO, approaching the theoretical capacitance of this material. A suitable combination of nanocrystalline grain size and the high surface area akin to the tubular structure is responsible for this high performance. In contrast, the NiO NR structure is characterized by lower performance (797 F/g). A further attribute of the proposed structure is its high stability against galvanostatic charging-discharging cycling at high current densities, with almost no alteration to performance after 500 cycles.